Low-frequency repetitive transcranial magnetic stimulation in patients with motor deficits after brain tumor resection: a randomized, double-blind, sham-controlled trial - Engelhardt, Melina; Schneider, Heike; Reuther, Jan; Grittner, Ulrike; Vajkoczy, Peter; Picht, Thomas; Rosenstock, Tizian (Frontiers in Oncology, 2024)
Objective: Surgical resection of motor eloquent tumors poses the risk of causing postoperative motor deficits which leads to reduced quality of life in these patients. Currently, rehabilitative procedures are limited with physical therapy being the main treatment option. This study investigated the efficacy of repetitive navigated transcranial magnetic stimulation (rTMS) for treatment of motor deficits after supratentorial tumor resection.Methods: This randomised, double-blind, sham-controlled trial (DRKS00010043) recruited patients with a postoperatively worsened upper extremity motor function immediately postoperatively. They were randomly assigned to receive rTMS (1Hz, 110% RMT, 15 minutes, 7 days) or sham stimulation to the motor cortex contralateral to the injury followed by physical therapy. Motor and neurological function as well as quality of life were assessed directly after the intervention, one month and three months postoperatively.Results: Thirty patients were recruited for this study. There was no significant difference between both groups in the primary outcome, the Fugl Meyer score three months postoperatively (Group difference [95%-CI]: 5.05 [-16.0; 26.1]; p=0.631). Patients in the rTMS group presented with better hand motor function one month postoperatively. Additionally, a subgroup of patients with motor eloquent ischemia showed lower NIHSS scores at all timepoints.Conclusions: Low-frequency rTMS facilitated the recovery process in stimulated hand muscles, but with limited generalization to other functional deficits. Long-term motor deficits were not impacted by rTMS. Given the reduced life expectancy in these patients a shortened recovery duration of deficits can still be of high significance.